Collaborative work and directorial pedagogical leadership in a Fe and Alegría school - Arbañil Barrientos, Milagros (2019)
The purpose of this research was to determine the relationship between directorial pedagogical leadership and collaborative work at Fe y Alegría School No. 12 in the Puente Piedra district of the department of Lima. The type of investigation was correlational and descriptive level; In addition, the technique used is the collection of data that was applied through surveys, with two questionnaires as instruments, one for each variable. Both consist of 20 items and work with the Likert scale (never, almost never, sometimes, almost always, always) whose index is 1, 2, 3, 4 and 5, respectively. These were applied to a sample of 54 individuals that was equal in number to the population, among management team, teachers and parents, whose information collected allowed to verify the hypotheses. As part of the study, the correlation of the directorial pedagogical leadership variable in its charismatic - emotional, anticipatory, professional - cultural, participative, formative and administrative dimensions with the collaborative work variable was determined, obtaining as a result a positive correlation of 0.721, 0.788, 0.779 , 0.796, 0.781, 0.737 and 0.692, respectively. With this it was possible to determine that the directorial pedagogical leadership is significantly related to the collaborative work of the school.